GRAPHS WITH THE BURNING NUMBERS EQUAL THREE - Li, Wen (International Journal of Research -GRANTHAALAYAH, 2023)
The concept of burning number is inspired by the firefighting problem, which is a new measure to describe the speed of information spread. For a general non-trivial connected graph